Data for: Paired with responsibility: Non-alcoholic beers are less liked when tasted alone but perform just as well as in food pairing - Scander, Henrik; Swahn, Johan; Baptista, Iuri (Örebro University, 2026)
This dataset contains the results of a consumer sensory test with 66 participants evaluating three beer types (a pilsner, an IPA, and a wheat beer) in their alcoholic (AL) and non-alcoholic (NA) versions, a total of six beers. All participants tasted each beer sample twice, first alone, then paired with skagenröra, a traditional Swedish shrimp salad. Participants evaluated liking using a 7-points hedonic scale; and flavor intensity, sourness, and bitterness using a 5-points just-about-right (JAR) scale. The data was collected at campus Grythyttan of Örebro University, Sweden, in November of 2025.

Denna datauppsättning innehåller resultaten av ett sensoriskt konsumenttest med 66 deltagare som utvärderade tre öltyper (en pilsner, en IPA och en veteöl) i sina alkoholhaltiga (AL) och alkoholfria (NA) versioner, i totalt sex öl. Alla deltagare smakade varje ölprov två gånger, först ensamt, sedan i kombination med skagenröra. Deltagarna utvärderade smak med en 7-punkts hedonisk skala; och smakintensitet, surhet och beska med hjälp av en 5-punkts just-about-right (JAR) skala. Data samlades in på campus Grythyttan vid Örebro universitet i november 2025.
Data för: Paired with responsibility: Non-alcoholic beers are less liked when tasted alone but perform just as well as in food pairing
Keywords: non-alcoholic beverages; alkoholfria drycker; gastronomy; gastronomi; consumer research; konsumentundersökning; beer; öl; drink pairing; dryckesrekommendationer; food services; matservice; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap